Effects and safety of oral tolvaptan in patients with congestive heart failure: A systematic review and network meta-analysis. - Mei-Yi Wu; Tzu-Ting Chen; Ying-Chun Chen; Der-Cherng Tarng; Yun-Chun Wu; Hsien-Ho Lin; Yu-Kang Tu (PLoS ONE, 2017)
Aims Several studies reported treatment benefits of tolvaptan in patients with congestive heart failure (CHF). However, the optimal dosage remains unclear. We aimed to compare different dosage of tolvaptan to determine the optimal dosage in terms of the efficacy and safety. Methods We searched MEDLINE, PubMed, EMBASE, Cochrane CENTRAL and ClinicalTrials.gov through Aug 31, 2016. Randomized controlled trials (RCTs) comparing tolvaptan of different dosages or to placebo in patients with CHF were included. We used network meta-analysis to look for the optimal dosage in terms of effectiveness and safety. Urine output, body weight change and change in serum sodium were the main outcomes of efficacy. Adverse effects were the secondary outcomes. Quality was assessed by Cochrane risk-of-bias tool. Results Twelve RCTs reporting 14 articles with 5793 patients (mean age, 65.7 ± 11.9 years; 73.7% man) were included. Compared with placebo, the tolvaptan 30 mg had similar effects to tolvaptan 45-90 mg in terms of urine output (mean difference [MD] 2.03 liter; 95% confidence interval [CI] 1.3 to 2.71), body weight change (MD -1.12 kg; 95% CI -1.37 to -0.88) and change in serum sodium (MD 3.06 meq/L; 95% CI 2.43 to 3.68). Compared with placebo, tolvaptan of different dosage showed a non-significant higher risk of adverse effects. Conclusions These findings suggest that tolvaptan 30 mg and 45 mg may be the optimum dosage for CHF patients, because of its ability to provide favourable clinical results without greater adverse effects. However, tolvaptan is not beneficial for reducing all-cause mortality in CHF patients.